A CRITICAL ANALYSIS OF STRATEGIC MANAGEMENT IN HUMAN RESOURCE PRACTICES WITHIN THE CREATIVE INDUSTRY - Mutmainatur Rohmah (CV. Lafadz Jaya, 2024)
The creative industry depends profoundly on strategic human resource management (HRM) that fosters creativity, adaptability, and innovation. This study critically examines the role of strategic management in HR practices within the creative sector, emphasizing approaches that align talent development with the dynamic demands of this industry. Through a qualitative analysis of case studies and existing literature, this research identifies core HR strategies—such as talent acquisition, skill enhancement, and employee retention—that are tailored to the unique requirements of the creative field. The findings highlight that a strategic alignment of HR practices with organizational objectives yields competitive advantages. However, rapid technological advancements and high turnover rates present ongoing challenges for sustainable HR practices in this sector. This study contributes to the understanding of how strategic HR management can be optimized to enhance both employee satisfaction and organizational performance in creative industries.